The Influence of Perceived Usefulness and Ease of Internet Technology on Company Effectiveness in JABODETABEK - Nadia Yusni Mardiana; Natan Abiel Utomo; Yeni Rizki Amaliah (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
In this modern era, where technology is increasingly sophisticated. Many companies use the internet network as a means to facilitate the running of their business. Besides making work more effective, the internet can also increase the competitive advantage to compete with competitors. This research aims to analyze the effect of Perceived Ease of Use, Perceived Usefulness on Intention to Use. In this study, data was collected using questionnaires distributed online. This study's population is internet work users who live in JABODETABEK. The sample in this research was 148 respondents who were selected using the purposive sampling method. The techniques used to analyze this research include instrumental tests, namely validity tests, reliability tests, and multiple regression using SPSS 25. There is a positive influence of Perceived ease of use on intentions to use in digital marketing positive influence of Perceived usefulness on choices to use in digital marketing. Perceived ease of service can be a benchmark that someone believes and feels technology is understandable and easy to use